'More Social' Means 'More Flawed': How New Media is Contributing to the Breakdown of Polish Democracy - Jakubowski, Jakub; Pająk-Patkowska, Beata (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2022)
It is no coincidence that anti-democratic changes in the recent years in Poland occurred alongside the rapid development of social media. Technologically advanced methods of discourse management (e.g., behavioral targeting) have successfully exploited the poor understanding of social media mechanisms among Poles1 (Drzewiecki, 2010) and created a fertile ground for undermining liberal democracy. Social media have endangered public debate by facilitating the spread of hate speech, fake news, deep fakes, trivialization of public discourse, astroturfing,2 and the use of bots for propaganda purposes. It seems that in the young and unstable Polish democracy, the combination of anti-democratic forces and dynamic development of social media poses a unique threat to the development of society.

Antydemokratyczne przemiany w Polsce zbiegły się nieprzypadkowo z wejściem na nowy poziom rozwoju mediów społecznościowych. Zaawansowane technologicznie metody zarządzania dyskursem (np. poprzez targetowanie behawioralne) współistnieją z niską wiedzą Polaków na temat tego jak funkcjonuje świat social media4 i niechęcią do zdobywania wiedzy na ten temat wśród polskich rodzin (Drzewiecki 2010). Staje się to żyznym gruntem dla rozwoju negatywnych zjawisk z punktu widzenia demokracji. Hejt, fake news i deep fake, trywializacja i banalizacja, astroturfing, wykorzystywanie botów w celach propagandowych… można w nieskończoność wymieniać niebezpieczeństwa związane z wpływaniem działań w social media na debatę publiczną. Stawiamy hipotezę, że w przypadku demokracji tak młodej i chwiejnej jak Polska, połączenie antydemokratycznych wizji państwa z tak dynamicznym rozwojem mediów społecznościowych stanowi wyjątkowe zagrożenie dla rozwoju społeczeństwa.
"Bardziej społeczne" oznacza "bardziej wadliwe": jak nowe media przyczyniają się do upadku polskiej demokracji
Keywords: social media; democracy; flawed democracy; media; fake news; populism; media społecznościowe; demokracja; media; populizm